2020
DOI: 10.1089/scd.2019.0260
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Wnt Signaling Pathway and Synovial Stem Cell Dysfunction in Osteoarthritis Development

Abstract: Stem cell dysfunction and failure have been found in joints afflicted by osteoarthritis (OA). However, the exact factors in the OA microenvironment that impair stem cell functions and the role of stem cell dysfunction in OA development have not been fully clarified. In this study, we evaluated the functional status of synovial mesenchymal stem cells (SMSCs) from OA patients and explored the influence of OA-SMSCs on cartilage degradation in a rat model. We then screened 138 Wnt signaling-related genes in the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
3
26
2
Order By: Relevance
“…Cellular functions of Vangl2 have been explored for more than two decades since Vangl2/Stbm was first identified in Drosophila [24]. A previous study in human revealed that the expression of Vangl2 increased in the OA synovium [17]. Thus, our finding that Vangl2 was significantly increased in OA chondrocytes raised the question of whether Vangl2 plays a role in OA progression.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Cellular functions of Vangl2 have been explored for more than two decades since Vangl2/Stbm was first identified in Drosophila [24]. A previous study in human revealed that the expression of Vangl2 increased in the OA synovium [17]. Thus, our finding that Vangl2 was significantly increased in OA chondrocytes raised the question of whether Vangl2 plays a role in OA progression.…”
Section: Discussionmentioning
confidence: 76%
“…Van Gogh-like 2 (Vangl2) is a core PCP component that regulates Wnt/PCP signaling [12][13][14][15]. Recently, evidence has accumulated that the pathogenesis of OA is associated with abnormal activation of Wnt/PCP pathway, which regulates the expression of MMPs and cartilage-related genes [9,10,[16][17][18]. Notably, previous research suggested that Vangl2 plays a crucial role in cartilage development and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular functions of Vangl2 have been explored for more than two decades since Vangl2/Stbm was rst identi ed in Drosophila [24]. A previous study in human revealed that the expression of Vangl2 increased in the OA synovium [17]. Our nding that Vangl2 was also signi cantly increased in OA chondrocytes raised the question of whether Vangl2 plays a role in OA progression.…”
Section: Discussionmentioning
confidence: 88%
“…Cellular functions of Vangl2 have been explored for more than two decades since Vangl2/Stbm was rst identi ed in Drosophila [24]. A previous study in human revealed that the expression of Vangl2 increased in the OA synovium [17]. Thus, our nding that Vangl2 was signi cantly increased in OA chondrocytes raised the question of whether Vangl2 plays a role in OA progression.…”
Section: Discussionmentioning
confidence: 89%